Infusing Culture in English Learning: An Attempt to Preserve Cultural Heritages in Jayapura Municipality, Papua - Yektiningtyas, Wigati; Modouw, James (LLT Journal: A Journal on Language and Language Teaching, 2017)
Papua is rich with cultural heritages: hundreds of vernacular languages, tribes, folklores and other unique traditions. Unfortunately, these heritages are not recognized by the young generation anymore. Modernization, technology, and new comers are assumed as the background. As the capital of the province, Jayapura is the most influenced place for the changes. As an attempt to re-introduce and preserve the ancestors cultural heritages, cultural infusion in learning English (as one type of learning) is regarded important. From seven tribes living in Jayapura, as the first step, Sentani is chosen as the priority. This paper discusses English learning materials by infusing Sentani culture. Folktales are chosen as learning materials for Elementary School students, malo[1] for Junior High School students, the procedure to make kayi/ifa[2] for Senior High Schoo students. This infusion hopes that young generation is able to learn English as well as to acknowledge one of the cultural heritages of Papua. They can be strongly rooted in their culture and respect others culture.